Implementation Of Tax Payment Policy Using E-Billing At The Pratama Cirebon Tax Services Office - Cipto Dwiariyanto; Mukarto Siswoyo; Endang Sutrisno (Journal of Entrepreneur and Business, 2024)
The vastness of the region, the large population, and the dynamic of economic activity is a challenge in upholding taxation in Indonesia. Incompatibility ratio between tens of thousands of tax employees with millions of taxpayers (WP) resulted in less optimal implementation of taxation in Indonesia. Since the launch of the electronic tax payment system, the Tax Office does not directly require the underpaying taxpayers to use the system. So the taxpayer still feel foreign to the system. In 2016, the underpayment taxpayer is required to make payments using e-Billing. Lack of knowledge about the use of e-Billing and its reliance on internet connections that must always be stable, these constraints have a significant impact on the use of the e-Billing system. Based on the policy implementation model of Daniel Mazmanian and Paul A.Sabatair, the model of analysis conducted on the implementation of the policy of Tax Payment Using E-Billing In Tax Office Pratama Cirebon, which : Characteristics of the problem, Policy characteristics and Policy environment In conducting the research, researchers used descriptive qualitative research methods. The e-Billing policy is not yet optimal for the implementation in the community because not all people know the tax payment system using e-Billing. Kata Kunci: Tax Policy; Electronic Transaction; E-Billing